IMPLEMENTATION OF THE LEAKY PIPE GAME FOR EARLY CHILDHOOD COOPERATION SKILLS - Andini, Yuli Tri (INCARE, International Journal of Educational Resources, 2023)
The world of children is a world of play, where children, through playing, it can develop their abilities. Games are part of play and , the implementation of games in kindergarten is often carried out as a means of stimulating children's developmental abilities. The development of cooperative abilities is part of the development of children's social emotional abilities which is important to improve. This is because the ability to collaborate is a provision for being able to mingle with social society in the future. This research aims to determine the implementation of the leaky pipe game to improve the cooperative abilities of young children. This research method is descriptive-qualitative, data collection uses observation, interviews and documentation. The subjects in this research were children aged 5-6 years at An-Nur Glenmore Kindergarten. The results of the research show that the leaky pipe game can be used to improve the cooperative abilities of young children.